The moonlighting activities of dihydrolipoamide dehydrogenase: Biotechnological and biomedical applications. Issue 11 (23rd June 2021) - Fleminger, Gideon; Dayan, Avraham
Abstract: Dihydrolipoamide dehydrogenase (DLDH) is a homodimeric flavin‐dependent enzyme that catalyzes the NAD + ‐dependent oxidation of dihydrolipoamide. The enzyme is part of several multi‐enzyme complexes such as the Pyruvate Dehydrogenase system that transforms pyruvate into acetyl‐co‐A. Concomitantly with its redox activity, DLDH produces Reactive Oxygen Species (ROS), which are involved in cellular apoptotic processes. DLDH possesses several moonlighting functions. One of these is the capacity to adhere to metal‐oxides surfaces. This was first exemplified by the presence of an exocellular form of the enzyme on the cell‐wall surface of Rhodococcus ruber . This capability was evolutionarily conserved and identified in the human, mitochondrial, DLDH. The enzyme was modified with Arg‐Gly‐Asp (RGD) groups, which enabled its interaction with integrin‐rich cancer cells followed by "integrin‐assisted‐endocytosis." This allowed harnessing the enzyme for cancer therapy. Combining the TiO2 ‐binding property with DLDH's ROS‐production, enabled us to develop several medical applications including improving oesseointegration of TiO2 ‐based implants and photodynamic treatment for melanoma. The TiO2 ‐binding sites of both the bacterial and human DLDH's were identified on the proteins' molecules at regions that overlap with the binding site of E3‐binding protein (E3BP). This protein is essential in forming the multiunit structure of PDC. Another moonlighting activity of DLDH, which is described in this Review, is its DNA‐binding capacity that may affect DNA chelation and shredding leading to apoptotic processes in living cells. The typical ROS‐generation by DLDH, which occurs in association with its enzymatic activity and its implications in cancer and apoptotic cell death are also discussed. Abstract : DLDH is a homodimeric flavin‐dependent enzyme that catalyzes the NAD + ‐dependent oxidation of dihydrolipoamide. It possesses several moonlighting functions, among these are the capacity to adhere to metal‐oxides surfaces, DNA binding, and ROS production. The last two may be involved in oxidative stress processes inducing apoptosis. Modifying DLDH with RGD groups enabled harnessing the enzyme for cancer therapy, mediated by integrin‐assisted endocytosis.